Extracellular matrix glycoproteins and diffusion barriers in human astrocytic tumours - Zámecník, J; Vargová, L; Homola, A; Kodet, R; Syková, E (Neuropathology and applied neurobiology, 2004)
The extracellular matrix (ECM) and changes in the size and geometry of the extracellular space (ECS) in tumour tissue are thought to be of critical importance in influencing the migratory abilities of tumour cells as well as the delivery of therapeutic agents into the tumour. In 21 astrocytic neoplasms, the ECM composition was investigated in situ by the immunohistochemical detection of ECM glycoproteins (tenascin, laminin, vitronectin, fibronectin, collagen types I-VI). To explain the changes in ECS size and to detect barriers to diffusion in the tumour tissue, the ECM composition, the cellularity, the density of glial fibrillary acidic protein (GFAP)-positive tumour cell processes and the proliferative activity of the tumours were compared with the size and geometry of the ECS. The ECS volume fraction and the complex of hindrances to diffusion in the ECS (i.e. the tortuosity) were revealed by the real-time iontophoretic tetramethylammonium method. Increased proliferative activity of the tumours correlated with increased ECS volume fraction and tortuosity. The tortuosity of the tumour tissue was not significantly influenced by tumour cell density. Higher tortuosity was found in low-grade astrocytomas associated with the presence of a dense net of GFAP-positive fibrillary processes of the tumour cells. The increase in tortuosity in high-grade tumours correlated with an increased accumulation of ECM molecules, particularly of tenascin. We conclude that the increased malignancy of astrocytic tumours correlates with increases in both ECS volume and ECM deposition.
Keywords: glykoproteiny; buněčné dělení; Extracellular Matrix Proteins; Female; Iontophoresis; ženské pohlaví; Immunohistochemistry; nádory mozku; lidé; Glial Fibrillary Acidic Protein; Paraffin Embedding; difuze; Glycoproteins; Temporal Lobe; imunohistochemie; glioblastom; extracelulární matrix; Glioblastoma; iontoforéza; imunoenzymatické techniky; gliový fibrilární kyselý protein; spánkový lalok; Astrocytoma; Male; Aged; extracelulární matrix - proteiny; zalévání tkání do parafínu; Brain Neoplasms; Immunoenzyme Techniques; Extracellular Matrix; Diffusion; senioři; mužské pohlaví; Cell Division; astrocytom; Humans